Luminescence and thermal behaviors of free and trapped excitons in cesium lead halide perovskite nanosheets. Issue 21 (17th May 2018) - Lao, Xiangzhou; Yang, Zhi; Su, Zhicheng; Wang, Zilan; Ye, Honggang; Wang, Minqiang; Yao, Xi; Xu, Shijie
Abstract : Luminescence in CsPbBr3 nanosheets is revealed to stem from the radiative recombination of free and trapped excitons. The thermal behaviors of luminescence have been studied. Abstract : Very recently, all-inorganic perovskite CsPbX3 (X = Cl, Br, I) nanostructures such as nanoparticles, nanoplates, and nanorods have been extensively explored. These CsPbX3 nanostructures exhibit excellent optical properties; however, the photophysics involved is not yet clear. Herein, the emission properties and luminescence mechanism of CsPbBr3 nanosheets (NSs) were investigated using steady-state and time-resolved photoluminescence (PL) spectroscopic techniques. Moreover, two kinds of excitonic emissions (Peak 1 and Peak 2) are observed at low temperatures (<80 K) under the conditions of low excitation level. They are revealed to stem from the radiative recombination of trapped and free excitons by examining their spectral features and emission intensity dependences on excitation power. Thermally induced exchange between the two kinds of excitons is found and modeled quantitatively; this has led to the determination of an activation energy of 13 meV. Thermal redistribution of trapped excitons and thermal expansion-induced blueshift of the bandgap are jointly responsible for the abnormal temperature dependence of the position of Peak 1, whereas the latter is predominant for the monotonic blueshift of the position of Peak 2 with an increase in temperature. These results and findings shed some light on the complicated luminescence mechanism of CsPbBr3 NSs.